Cosmetic Surgery and the Christian Body: Comparative Ethical Reflections from Orthodox and Catholic Traditions - Mavropoulos, Angelos (Religions, 2025)
This article explores the ethical dimensions of cosmetic surgery, offering a comparative analysis of perspectives from both the Orthodox and the Catholic moral theologies. Both traditions uphold the sanctity of the human body as a creation of God, emphasizing the importance of maintaining its integrity and dignity. However, their approaches to the ethical implications of cosmetic surgery might reveal distinct theological nuances that reflect their unique doctrinal and cultural contexts. By examining the theological foundations, doctrinal teachings, and contemporary ethical debates within both traditions, this study seeks to illuminate how Orthodox and Catholic ethics address the complexities of bodily modification. The analysis highlights the ways in which each tradition navigates concerns related to vanity, identity, and the pursuit of physical perfection, offering insights into their shared values as well as their distinct perspectives. This interdenominational study aims to contribute to ecumenical and intercultural dialogue, fostering greater understanding and respect between the two original Christian traditions. By engaging with the ethical considerations surrounding cosmetic surgery, this article provides a platform for deeper reflection on the role of the body in Christian spirituality and the ongoing relevance of these issues in a diverse and interconnected world.